Transcriptomic and functional characterization reveals CsHAK5;3 as a key player in K+ homeostasis in grafted cucumbers under saline conditions - Peng, Yuquan (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2022 Elsevier B.V. All rights reserved.